Faktor-Faktor Yang Mempengaruhi Nilai Impor Kendaraan Bermotor Indonesia dari Jepang Periode 1990-2012 - Wijayanthi, Ketut Evilia; Mustika, Made Dwi Setyadhi (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
Import can not be separated from the influence of domestic demando n consumer godos and imports of raw and auxiliary materials, as well as capital godos whose supply can not be met entirely by domestic industries. One of the godos impoted by Indonesia is a motor vehicle. Development of motor vehicles imported from Japan to Indonesia period had an average growth of 31,38 percent per year. Purpose of this study was to determine the effect of gross domestic product (GDP), the US dollar Exchange reserves simultaneously and partially to the value of imports of Japanese motor vehicles Indonesia 1990-2012 period. By using multiple linear regression analysis get the results we concluded that the gross domestic product, the dollar exchange rate, inflation and foreign Exchange reserves simultaneously influence the value of imports of Japanese motor vehicles Indonesia 1990-2012 period. Partially dollar Exchange rate and inflation does not affect the value of imports, gross domestic product and the positive affect of foreign Exchange reserves, while the gross domestic product of variables known as the most dominant. Keyword
Keywords: Indonesia imports of motor vehicles from Japan, Gross Domestic Product (GDP), united states dollar exchange rate, inflation, foreign exchange reserves